Perlindungan Hukum Implementasi Asas Keseimbangan Perjanjian Jasa Pemborongan - Solihin Abdullah,; Muhammad Ervan Sidabutar; Yoga Ronaldo,; Abdurrachman Hidayat,; Eriandi (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2023)
Most directors are appointed by a competent agency, usually a general employment agency on the basis of assignment or assignment of a job in the public employment office by a government agency. The principle of balance in bribery contracts, the legal protection of incentives, and the role of the government as the party responsible for bribership contracts The studies used are included in the category of normative law research. In a mining service agreement, the application of the principle of balance is crucial to reaching a mutually beneficial agreement. Everyone has to do what they're asking. If the construction service provider fails to complete the work in time, the provider will be subject to a fine, which will be deducted from the last project fund. Construction service providers are expected to be free to claim their uncertain rights through a lawsuit to state courts if the commitment officer commits a discharge.